Towards coarse-grained modelling of proteins - Stepanova, M. (Condensed Matter Physics, 2007)
This paper introduces a basic theoretical background to the description of conformational dynamics of proteins through a system of interacting domains. The essential collective degrees of freedom derived by principal component analysis of a molecular dynamics trajectory are used as dynamic variables defining the projection operator technique that underlies the formalism suggested. The explicit form of the corresponding projection operator is obtained, and the projection method is employed to derive systems of coupled generalized Langevin equations for both individual atomic degrees of freedom and essential collective degrees of freedom in a protein. A definition of correlated domains in proteins is introduced based on the analysis of the essential dynamics. Examples of identification of such domains are presented. A system of coupled generalized Langevin equations is derived representing the protein through a few interacting domains embedded into a dissipative medium. Further developments and potential applications of the formalism are outlined.